Peptide Receptor Radionuclide Therapy Outcomes in a North American Cohort With Metastatic Well-Differentiated Neuroendocrine Tumors. Issue 2 (February 2017) - Sharma, Nancy; Naraev, Boris G.; Engelman, Eric G.; Zimmerman, M. Bridget; Bushnell, David L.; O'Dorisio, Thomas M.; O'Dorisio, M. Sue; Menda, Yusuf; Müller-Brand, Jan; Howe, James R.; Halfdanarson, Thorvardur R.
Abstract : Objectives: The objective of this study was to describe the outcomes of patients in the University of Iowa Neuroendocrine Tumor (NET) Database treated with peptide receptor radionuclide therapy (PRRT). Methods: One hundred thirty-five patients from the University of Iowa NET Database who received PRRT were analyzed, their characteristics were described, and survival was calculated. Results: The median age at diagnosis was 51 years, and 64% were men. The primary tumor was located in the small bowel (SBNET) in 37.8%, in the pancreas (PNET) in 26.0%, in the lung in 13.3%, in unknown primary in 9.6%, and in other sites in 13.3%. A radiographic response of any magnitude was observed in 65.8%, 11.1% had a mixed response, and 15.4% showed progression. The overall survival (OS) from the first PRRT was 40 months, and the median time to progression was 23.9 months. Higher pretreatment chromogranin A and pancreastatin levels predicted inferior OS. Conclusions: Peptide receptor radionuclide therapy resulted in a relatively long OS and time to progression in heavily pretreated North American patients with advanced NETs. Elevated pretreatment chromogranin A and pancreastatin predicted shorter OS after therapy. Peptide receptor radionuclide therapy is a valuable treatment option in patients with advanced NETs, especially SBNETS.